Spinal cord stimulation in the United Kingdom. - Illis, L S (1983)
All the medical, surgical and engineering personnel in the UK who have used spinal cord stimulation (SCS) in patients, attended a workshop to discuss their results. The major use of SCS has been for multiple sclerosis and intractable pain. It was concluded that the technique benefited up to two thirds of patients with bladder dysfunction, and that pain and possibly spasticity also responded to SCS, but other manifestations of multiple sclerosis did not. Further information on long term benefit is needed and the use of SCS in other conditions, such as spinal injury and peripheral vascular disease, is not yet established. SCS cannot be recommended for use outside large centres as x-ray screening, urodynamic and neurophysiological assessment facilities are required as well as biological engineering assistance.